The consistency between professed teaching practices and assessment practices: a case in mathematics class - Darwis, Sutawanir; Suryadi, Didi; Ismail, Siti Noor; Kaur, Amrita; Purnomo, Yoppy Wahyu (Beta: Jurnal Tadris Matematika, 2018)
The purpose of this research was to (1) develop scales for measuring teaching practices and assessment practices in mathematics class; (2) identify the profile of teaching practices and assessment practices in mathematics class; and (3) examine the consistency between relevant factors in teaching practices and assessment practices in mathematics class. The methods of cross-sectional surveys and a scale development study were used to achieve that purpose. The participants in this research included two sample groups of primary school teachers in Jakarta. The first sample consisted of 252 teachers and the second sample consisted of 325 teachers. This research found that there were two factors in each dimension of teachers’ practices in mathematics class. Teaching practices included the relational and instrumental practices, while the assessment practices included the assessment for learning and assessment of learning. This research also found that most of the teachers leaned toward traditional practices for both teaching practices and assessment practices, and that there was a consistency between relevant factors in those teaching and assessment practices. A more detailed discussion can be found in the findings and discussion section.